2010
DOI: 10.1016/j.ajhg.2010.10.026
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous Mutation in the Tight-Junction Protein JAM3 Causes Hemorrhagic Destruction of the Brain, Subependymal Calcification, and Congenital Cataracts

Abstract: The tight junction, or zonula occludens, is a specialized cell-cell junction that regulates epithelial and endothelial permeability, and it is an essential component of the blood-brain barrier in the cerebrovascular endothelium. In addition to functioning as a diffusion barrier, tight junctions are also involved in signal transduction. In this study, we identified a homozygous mutation in the tight-junction protein gene JAM3 in a large consanguineous family from the United Arab Emirates. Some members of this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 35 publications
6
78
1
Order By: Relevance
“…JAM-C −/− mice in the C57BL/6 genetic background developed a severe and progressive hydrocephalus, characterized by extremely enlarged lateral ventricles accompanied by hippocampal dislocation, cortical thinning, loss of proper cortical layering with subsequent reactive gliosis as well as hemorrhages in different brain compartments and obstruction of CSF circulation. In contrast to JAM-C −/− mice in mixed 129Sv - C57BL/6 background, JAM-C −/− C57BL/6 mice therefore mimic part of the CNS pathology recently observed in members a large consanguineous family carrying a rare mutation in JAM-C leading to a non-functional protein [19]. Affected individuals develop a syndrome characterized by severe hemorrhagic destruction of the brain, sub-ependymal calcifications, enlarged ventricles and congenital cataracts partially reflected in JAM-C −/− C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 64%
“…JAM-C −/− mice in the C57BL/6 genetic background developed a severe and progressive hydrocephalus, characterized by extremely enlarged lateral ventricles accompanied by hippocampal dislocation, cortical thinning, loss of proper cortical layering with subsequent reactive gliosis as well as hemorrhages in different brain compartments and obstruction of CSF circulation. In contrast to JAM-C −/− mice in mixed 129Sv - C57BL/6 background, JAM-C −/− C57BL/6 mice therefore mimic part of the CNS pathology recently observed in members a large consanguineous family carrying a rare mutation in JAM-C leading to a non-functional protein [19]. Affected individuals develop a syndrome characterized by severe hemorrhagic destruction of the brain, sub-ependymal calcifications, enlarged ventricles and congenital cataracts partially reflected in JAM-C −/− C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 64%
“…6466 Familial occurrence of the FBDS phenotype has also been reported, and for these cases, the term fetal brain arrest has been proposed. 6769 …”
Section: Differential Diagnosismentioning
confidence: 99%
“…JamC has been implicated in angiogenic responses although its specific functional purpose during these events was unclear [Lamagna et al, 2005]. A recent study demonstrated mutations in JamC that lead to neonatal lethality in humans due to vascular abnormalities and hemorrhage, particularly in the central nervous system [Mochida et al, 2011]. JamB and JamC are known to interact with each other and, through their cytoplasmic tails, are known to bind the polarity protein Par3 [Ebnet et al, 2003[Ebnet et al, , 2004.…”
Section: Jamb and Jamc Interact With The Polarity Protein Par3 To Conmentioning
confidence: 99%